Sosialisasi Potensi Dan Peluang Kerja Di Kabupaten Lima Puluh Kota - Nelvi, Afni; Hisni Rahmi; Marlina Amsya, Riam; Fadhly, Ahmad; Nofriadiman Nofriadiman; Elmawati Elmawati; Ervil, Riko; Mariza Syahyuda, Nelsy (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Based on data from the West Sumatra energy and mineral resources service, it is stated that Limapuluh Kota Regency has the potential for rocks (andesite, granite, limestone, marble) and metallic minerals (gold and lead). This huge natural potential requires good management so that it can develop and requires potential human resources as well. This is the background for socializing opportunities and potential job opportunities in Limapuluh Kota Regency. The socialization explains what potential mining resources exist in Limapuluh Kota Regency along with the job opportunities that exist in managing these resources. The target of this socialization is to open the minds of high school students in terms of the natural potential that their region has and to open up the students' insight in choosing the science they will study in college, so that as sons/daughters of the region they can contribute to the management and development of their region.